1985
DOI: 10.1002/aja.1001720107
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative ultrastructural characteristics relating to transport between luteal cell cytoplasm and blood in the corpus luteum of the pregnant rat

Abstract: The synthesis and secretion of progesterone by the corpus luteum (CL) may be limited or controlled by transport mechanisms operating between circulating blood and luteal cell cytoplasm. To examine this possibility, the structural features involved in transport, including membrane surface areas and diffusion distances, were quantitated in the CL of 16-day pregnant rats. One ovary from each of eight rats was fixed by perfusion via a cannula inserted into the parametrial artery, and two CL from each ovary were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
1

Year Published

1986
1986
2010
2010

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 23 publications
4
25
0
1
Order By: Relevance
“…The vascular density (VD) is another important parameter, which reflects vascularization of the tissue and, consequently, its blood perfusion level (Dharmarajan et al 1985, Asahara et al 1995. The study of VD in the CL of goats confirmed that, apart from the macroscopic and microscopic changes in the luteal structure, changes in the vascular network during the estrous cycle were observed, which reflected the functional activity of the organ.…”
Section: Discussionmentioning
confidence: 78%
“…The vascular density (VD) is another important parameter, which reflects vascularization of the tissue and, consequently, its blood perfusion level (Dharmarajan et al 1985, Asahara et al 1995. The study of VD in the CL of goats confirmed that, apart from the macroscopic and microscopic changes in the luteal structure, changes in the vascular network during the estrous cycle were observed, which reflected the functional activity of the organ.…”
Section: Discussionmentioning
confidence: 78%
“…4 animals is reported to have a probability of P , 0.05 (Cruz-Orive & Weibel 1990). Secondly, the effects of fixation cause significant cell shrinkage and affect measurement of vascular space (Dharmarajan et al 1983(Dharmarajan et al , 1985. Since luteal weights and the consistency of luteal tissue varied with both treatment group and stage of luteal phase, fixation effects may vary between treatment groups and luteal stage.…”
Section: Morphology Of the CLmentioning
confidence: 99%
“…Das Corpus luteum wird stark durchblutet und gehört zu den Organen mit dem höchsten Blutfluss. Jede Lutealzelle steht in direktem Kontakt mit einem dichten Kapillarnetz [27]. Das Corpus luteum hat in Relation zu seinem Gewicht einen 2-bis 6-fach höheren Sauerstoffverbrauch als beispielsweise die Leber, die Niere oder das Herz [31].…”
Section: Bildung Des Corpus Luteumunclassified